Nitrous oxide use during colonoscopy: a national survey of English screening colonoscopists. Issue 4 (15th April 2014) - Ball, Alex J; Campbell, Jennifer A; Riley, Stuart A
Abstract : Introduction: Nitrous oxide can improve patient experience during colonoscopy, and its rapid elimination minimises after effects and inconvenience. Despite its advantages, nitrous oxide is used infrequently in the UK. We sought to understand the reasons for its low use. Methods: Colonoscopists within the English Bowel Cancer Screening Programme (BCSP) were invited to participate in a web-based survey assessing the availability, current practices and perceptions towards nitrous oxide. Respondents were able to select predefined answers or offer written responses. Free text responses were assessed using thematic analysis. Results: The survey was completed by 68% of the English BCSP colonoscopists. Nitrous oxide was available to 73% of respondents but with considerable regional variation. Most colonoscopists rated the properties of nitrous oxide favourably and would use it if they had a colonoscopy themselves. Despite this, nearly half used it in less than 20% of examinations. 80% instruct patients to use nitrous oxide as required, and differences in how it was used in combination with intravenous sedation and analgesia were reported. Written responses suggest nitrous oxide is often used in the patients who are expected to have the least discomfort. Conclusions: Most colonoscopists perceive that nitrous oxide is effective and reduces inconvenience and would use it themselves if they required a colonoscopy. Studies to improve patient selection and optimise the use of nitrous oxide would be of value.